Technology-based Project-based Learning to Teach English in University Level: Need Analysis - Desak Made Anggun Srie Durita Devy; Ni Nyoman Padmadewi; Ketut Sintya Dewi (Linguistic, English Education and Art (LEEA) Journal, 2023)
The goal of this study is to create a conceptual framework for implementing project-based learning in private institutions to teach language skills. This study made use of the LPKS Aura Sukma Insani-Tourism and the Home Assistance Program in the English study program. An explanatory mixed methods design method was used in this study, with quantitative research and qualitative analysis conducted to support the analysis. The needs analysis model is a hybrid of CIPP and OEM evaluation concepts. According to the findings of this study, this institution in this context requires a conceptual framework for the use of technology-based Project-based learning in teaching language skills, so that trainers are pedagogically prepared. The input results indicate that this institution requires trainers and students to be prepared to implement technology-based Project-based learning in the classroom. The process results indicate that technology-based project-based learning must be implemented with adequate technological support for students. The product results demonstrate that this technology-based project-based learning must be capable of producing results in the form of products that will later be used as evaluation material in the implementation of additional technology-based project-based learning. In addition to the findings of the analysis, it was discovered that the planning of teaching materials must be in accordance with student needs as well as 21st century skills. Keywords: language skill, project-based learning, technology, 21st century learning